Literature Review: Efficacy of Tuberculosis Preventive Treatment and Utilization of its Services in Indonesia - Vasya Iftita Shabrina; Retno Asih Setyoningrum; Samsriyaningsih Handayani (Faculty of Medicine, 2026)
Tuberculosis (TB) is an infectious disease that causes a high mortality rate worldwide, with Indonesia ranking second in the number of TB cases. Tuberculosis Preventive Therapy (TPT) is a key strategy to prevent the progression of active TB in individuals with latent TB infection. Various treatment regimens, such as 6H, 3HP, and 3HR, show varying efficacy in preventing the progression to active TB. The 6H regimen, using Isoniazid for six months, has proven effective; however, the long treatment duration affects patient adherence. Alternatively, the shorter 3HP and 3HR regimens (three months) provide similar results to 6H and can improve patient adherence due to the shorter treatment duration. Nevertheless, factors such as patient understanding, social stigma, and access to healthcare facilities remain major barriers to the successful implementation of the TPT program in Indonesia. This literature review emphasizes the importance of a patient-centered approach, the selection of shorter regimens, and strengthening the healthcare system to enhance the effectiveness of the TPT program in reducing active TB cases in Indonesia